Size and independence of the board of directors and its relationship with economic performance: an analysis for family and non-family businesses (2017)
The purpose of this research paper is to determine the effect of the size and independence of the board of directors on economic performance of family and non-family businesses in Colombia. The relationship was analyzed using regression models in a balanced panel data based on three aspects (size and independence of the board of directors and family nature of the company). The sample comprised 2,170 observations (310 businesses a year) between 2008 and 2014. It was found that: (i) the size of the board of directors has a negative influence on the ROA, ROE in the family companies; (ii) there is a positive influence from the independent members of the board of directors in the operatingincome (OI) for both family and non-family businesses; and (iii) the family nature shows a positive influence in the ROA indicator; however, the relationship is negative when they are first-generation family businesses. On the basis of the empirical findings, it is suggested that the control entities promote campaigns to disseminate the impact of the board of directors and the adequate role of independent members on the companies’ performance, and entrepreneurs are welcomed to implement good corporate governance practices.